2020
DOI: 10.1038/s41598-020-61472-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of atrophic gastritis in southwest China and predictive strength of serum gastrin-17: A cross-sectional study (SIGES)

Abstract: A hospital-based cross-sectional study in SIGES project was conducted during 2016.5-2017.5 in West China Hospital. It was aimed to observe the prevalence of atrophic gastritis (AG) in southwest China, and assess the diagnostic strength of serum gastrin-17 (G-17) in predicting AG in Chinese population. Asymptomatic healthy controls from health checkup , cancer-free patients with unspecific upper gastrointestinal symptoms, and histologically proven gastric cancer patients were eligible, if serum pepsinogen-I (PG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 45 publications
(31 reference statements)
2
17
1
1
Order By: Relevance
“…In the screening of gastrointestinal diseases, PGI 70 ng/mL and PGR 3 was a commonly accepted cutoff [10]. In fact, many studies have defined the thresholds of serum PGs based on the characteristics of the data [24,33,34]. It has been reported that the cutoff value of PGI was 123 ng/mL in the aspirin-induced gastroduodenal injury [24].…”
Section: Discussionmentioning
confidence: 99%
“…In the screening of gastrointestinal diseases, PGI 70 ng/mL and PGR 3 was a commonly accepted cutoff [10]. In fact, many studies have defined the thresholds of serum PGs based on the characteristics of the data [24,33,34]. It has been reported that the cutoff value of PGI was 123 ng/mL in the aspirin-induced gastroduodenal injury [24].…”
Section: Discussionmentioning
confidence: 99%
“…According to the consensus on chronic gastritis in China published in 2017 [19], the levels of serum PGI, PGII, PGR, and G-17 could be used to accurately distinguish the secretion features, atrophy degrees, and tissue function of gastric mucosa in different areas. us, the measurement of these markers has been recognized as a reliable noninvasive method for diagnosing gastric mucosal diseases in early stages [6,33]. Several previous studies indicated that the levels of PGI and PGR were positively correlated with the severity of corpus gastritis [34][35][36][37], while the level of G-17 decreased with the aggravation of antral inflammation and 8 Evidence-Based Complementary and Alternative Medicine atrophy [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, disease recurrence after drug withdrawal, antibiotic resistance after long-term medication, and several other side effects complicate the treatment of CG [3][4][5]. Long-term nonatrophic CG is very likely to progress into atrophic CG, which is a recognized precursor of gastric cancer [6].…”
Section: Introductionmentioning
confidence: 99%
“…G-17 is a predominant form of antral hormone gastrins in plasma or tissue in antral mucosa, which can regulate gastric acid secretion and gastric mucosa growth. Wang et al reported that elevated serum G-17 level was significantly associated with an increased risk of AG in healthy people ( 29 ). However, the diagnostic ability of serum G-17 level for AG decreased at higher levels during the whole process of gastric disease ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported that elevated serum G-17 level was significantly associated with an increased risk of AG in healthy people ( 29 ). However, the diagnostic ability of serum G-17 level for AG decreased at higher levels during the whole process of gastric disease ( 29 ). In the present study, there were significant differences in PG I, PG II, PGR, and G-17 among the nonatrophic gastritis, OLGA stages I–II and III–IV subgroups.…”
Section: Discussionmentioning
confidence: 99%